Character Education Values on Alice's Characterization in The Alice's Adventures in Wonderland by Lewis Carroll - Kristiyani; Juniarta, I Putu Adi Krisna; Mahendrayana, I Gede (International Journal of Language and Literature, 2021)
Education is an essential need for human character building. Education also can be one of the methods used to maintain the cultural heritage and national character of the young generation. However, the quality of education is needs to be considered in develop good nation. If the education is lack of quality, it makes negative affect for future generations, such as the emergence of the phenomenon of character degradation. This study aimed to identify character education values on Alice’s characterization in the children’s literature entitled Alice’s Adventures in Wonderland (1865) by Lewis Carroll. The values of character education in this study formulated by the Ministry of Education and Culture of Indonesia (2017) which have five core values, they are religious, nationalist, independent, cooperative, and integrity. This study used descriptive qualitative approach by Miles and Huberman (1994) in an interactive model that is divided into four steps, namely data collection, data reduction, data display, and conclusion drawing/verification. The researcher found that there are 20 characters of Alice’s characterization that present direct and indirect; and there are 13-character education values from Alice’s characterization.